IoT based car parking management system using IR sensor / Muhamad Muzhafar Abd Kadir... [et al.] - Abd Kadir, Muhamad Muzhafar; Osman, Mohd Nizam; Othman, Nor Arzami; Sedek, Khairul Anwar (UiTM Cawangan Perlis, 2020)
This paper proposes an IoT based Car Parking Management System that is developed to display the vacant or available parking slot. It integrates a nodeMCU as microcontroller with IR sensor and LCD screen. The IR sensor is used to detect the absence or presence of a car when it enters the parking slot, and the LCD screen is then used to display the vacant parking slot to the driver. The parking slots are continuously monitored, and the data is continuously updated in the LCD screen. The proposed parking system is developed using the Internet of Things (IoT) technology with the minimum cost, effective and efficient. The main purpose of the proposed parking system is to help or assist drivers in finding a vacant parking slot. Furthermore, the proposed parking system can also record the availability status of parking slot and the exact time a car enters or exits a parking slot in the database for the use of the administrative management. Thus, it also helps the drivers in reducing their time spent in finding vacant parking slots. As such, the drivers save their energy and will help reduce the traffic congestion in the parking area. The prototype for proposed parking system was developed to visualize and stimulate the real parking system environment, and a demonstration of the prototype has proven the capability of the system to reserve the exact location of the parking slot by displaying on the LCD screen. Then, a user acceptance test was conducted with 30 respondents to determine the effectiveness of the prototype for the proposed parking system. The result obtained from the testing was positively accepted by most of the participants. Therefore, the proposed parking system has been proven to be beneficial to the drivers and can also motivate other developers to contribute to more future projects to help the drivers in finding a vacant parking slot easily.